A method for synergistically improving the strength and plasticity of multi-component alloy laser additive manufacturing

CN120961943BActive Publication Date: 2026-10-27XI AN JIAOTONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511147339.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-15
Publication Date
2026-10-27
Estimated Expiration
2045-08-15

AI Technical Summary

Technical Problem

[0006]本申请提供一种多组元合金激光增材制造强塑性协同提升方法,旨在解决现有技术降低材料的断裂韧性与抗疲劳性能;同时常规单一热处理制度难以实现析出强化与相变塑性的协同优化,造成强度衰减的问题

Benefits of technology

[0027]本申请基于对现有技术问题的进一步分析和研究,通过采用交变磁场使合金成品析出相分布更加均匀化,有效避免了晶界脆化现象,且能够抑制晶粒长大,诱导应变诱导孪晶的形成,进一步优化了合金的强塑性配合,同时,通过磁场辅助多级热处理,促进FCC→HCP应变诱导相变,最终形成含有FCC与HCP的双相组织合金成品,提升合金的加工硬化能力,增强合金的塑性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120961943B_ABST
    Figure CN120961943B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of multi-component alloy additive manufacturing strong plasticity, and discloses a multi-component alloy laser additive manufacturing strong plasticity synergistic improvement method. The method comprises the following steps: S1: preparing main alloy powder through each component, then preparing an intermediate alloy ingot by mixing Si and Ti in proportion, and mixing the intermediate alloy ingot with the main component metal after crushing; S2: in the process of laser selective melting forming, the alloy component is formed finally by using an ultrahigh scanning speed of 25-30 m / s and an ultrathin layer thickness of 0.02 mm for layer-by-layer accumulation; S3: the alloy component is heated to 500-530 DEG C in a gradient temperature control furnace, and is kept for 1.5-2 h, and an alternating magnetic field is started synchronously to drive Ti atomic diffusion. The application makes the distribution of alloy finished product precipitated phase more uniform by using an alternating magnetic field, effectively avoids the grain boundary embrittlement phenomenon, and can inhibit the grain growth, further optimizes the strong plasticity of the alloy, and at the same time, the magnetic field assisted multi-stage heat treatment improves the work hardening capacity of the alloy and enhances the plasticity of the alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of high plasticity technology in multi-component alloy additive manufacturing, specifically relating to a method for synergistic improvement of high plasticity in multi-component alloy laser additive manufacturing. Background Technology

[0002] In the field of materials science, multi-principal element alloys (such as medium / high entropy alloys) have attracted much attention due to their unique physicochemical properties. These alloys exhibit outstanding mechanical performance potential based on characteristics such as high entropy effects, lattice distortion, and hysteresis diffusion effects. Among them, FeCoNi-based medium-entropy alloys, as a typical representative system, exhibit good toughness at low temperatures. With the accelerated advancement of new energy technology innovation driven by dual carbon and deep space exploration projects, FeCoNi-based medium-entropy alloys, in the field of liquefied natural gas storage and transportation equipment, can perfectly solve the problem of brittle fracture under ultra-low temperature conditions due to their excellent low-temperature toughness. Especially in high-performance bearing systems for spacecraft, this alloy maintains stable size effects and wear resistance across a wide temperature range, significantly improving the operational life of satellite payload equipment.

[0003] With the continuous progress of my country's aviation industry, strategic equipment such as launch vehicles, manned spacecraft, and aero engines are developing towards larger, lighter, more complex, and integrated structural and functional design and manufacturing, which puts forward more stringent requirements and challenges to traditional manufacturing processes. Therefore, it is necessary to use a method for synergistic improvement of strength and plasticity in multi-component alloy laser additive manufacturing of FeCoNi.

[0004] For example, Chinese patent publication number CN 112301255 B discloses a high thermal conductivity and high strength Co-Fe-Ni alloy for molds and its additive manufacturing method. It discloses a Co-Fe-Ni alloy that improves thermal conductivity and service reliability by using additive manufacturing and subsequent heat treatment to control different combinations of strength and toughness without significantly increasing costs and maintaining the same mechanical properties as existing mold steels.

[0005] However, most current methods for synergistically improving the strength and plasticity of multi-component alloy laser additive manufacturing, when using additive manufacturing technology, are prone to uneven micro-distribution of elements due to the rapid non-equilibrium solidification process. Alloy elements tend to be abnormally enriched in the grain boundary region, forming a continuous brittle phase network, which reduces the fracture toughness and fatigue resistance of the material. At the same time, conventional single heat treatment regimes are difficult to achieve synergistic optimization of precipitation strengthening and phase transformation plasticity. For example, although high-temperature annealing can refine grains and improve plasticity, it can also cause coarsening or even dissolution of precipitates, resulting in strength reduction. Summary of the Invention

[0006] This application provides a method for synergistically improving the strength and plasticity of multi-component alloy laser additive manufacturing, aiming to solve the problem that existing technologies reduce the fracture toughness and fatigue resistance of materials; at the same time, conventional single heat treatment processes are difficult to achieve synergistic optimization of precipitation strengthening and phase transformation plasticity, resulting in strength attenuation.

[0007] A method for synergistically improving the strength and plasticity of multi-component alloy laser additive manufacturing, the method comprising the following steps:

[0008] S1: The main alloy powder is prepared by various components, and then Si and Ti are made into intermediate alloy ingots in a certain proportion, which are crushed and mixed with the main metal; the components include Fe, Co and Ni elements, with Fe at a mass of 28-32%, Co at a mass of 28-32%, Ni at a mass of 36-40%, Si at a mass of 0.08-0.2%, and Ti at a mass of 0.04-0.1%;

[0009] S2: During the laser selective melting and forming process, an ultra-high scanning speed of 25-30m / s is used in conjunction with an ultra-thin layer thickness of 0.02mm to stack layer by layer, and an anisotropy is eliminated by a 67° interlayer rotation strategy; finally, an alloy component with a honeycomb dislocation cell structure is formed.

[0010] S3: The alloy component is placed in a gradient temperature controlled furnace and heated to 500-530℃ and held for 1.5-2 hours. Simultaneously, an alternating magnetic field is started to drive Ti atoms to diffuse in a directional manner, forming a uniformly distributed coherent L12-Ni3Ti nanoprecipitate phase.

[0011] S4: Transfer the alloy sample that has undergone low-temperature aging treatment to the medium-temperature treatment area of ​​the gradient temperature control furnace, heat it to 780-800℃, and hold it for 1.2-1.5h. Turn on the alternating magnetic field generator and apply a strong magnetic field.

[0012] S5: After the heat preservation is completed, the high-pressure nitrogen jet cooling device is quickly started to perform water cooling treatment on the alloy components at a high-speed cooling rate of >150℃ / s, and finally form a duplex alloy product containing FCC and HCP.

[0013] Furthermore, S1 specifically includes the following steps:

[0014] S1.1: Clean each component sequentially with acetone using ultrasonic cleaning for 15-20 minutes, rinse with deionized water, dehydrate with anhydrous ethanol, and then place in a vacuum drying oven to remove residual solvent. The temperature of the vacuum drying oven is 85-95℃, and the drying time is 2.5-3 hours.

[0015] S1.2: Using a planetary high-energy ball mill with zirconia ceramic balls as the grinding medium, the ball mill is carried out for 4.5-5 hours under the protection of anhydrous ethanol, and then sieved to obtain the main alloy powder with a particle size of 15-45μm.

[0016] S1.3: Si and Ti powders with a mass ratio of 1:0.5 are unidirectionally pressurized to 300MPa in a steel mold and held for 5-10 minutes to form a cylindrical blank with dimensions of 30mm×10mm;

[0017] S1.4: Place the cylindrical blank in a vacuum sintering machine at a temperature of 800-850℃ and hold for 1-1.2 hours to remove the adsorbed gas. Then raise the temperature to 1250-1300℃ and hold for 2-2.2 hours.

[0018] S1.5: The cooled Si and Ti powders are initially crushed to <5mm particles using a jaw crusher, and then wet-ground to <1mm particle size using a planetary mill to obtain intermediate alloy powder.

[0019] S1.6: Add the main alloy powder to the ball mill, then add the intermediate alloy powder, and add 0.5% stearic acid. Dry ball mill for 1.2-1.5 hours at a speed of 200-250 rpm.

[0020] Furthermore, the stearic acid is used to prevent electrostatic adsorption of the powder.

[0021] Furthermore, the laser generator has an output power of 850–950W, and before starting the laser selective melting and forming, a worktable carrying pre-alloyed powder is first sent into the forming chamber, and a powder layer with a thickness of 0.02–0.04 mm is evenly laid by a scraper system.

[0022] Furthermore, when the alloy component is heated to 500-530°C in a gradient temperature-controlled furnace, the oscillating electromagnetic field generated by the alternating magnetic field will induce eddy current effects inside the metal, continuously perturbing the lattice atomic arrangement through the Lorentz force, thereby reducing the diffusion activation barrier of Ti atoms.

[0023] Furthermore, the strong magnetic field parameters are 1.2T and 10Hz, and the direction of the strong magnetic field is arranged along the key force direction of the alloy component, so as to make the strong magnetic field interact with the atoms and electrons in the alloy, thereby changing the binding force and motion state of the atoms and electrons.

[0024] Furthermore, the parameters of the alternating magnetic field are 0.8T and 20Hz, which are used to suppress grain boundary migration and avoid coarsening of precipitates.

[0025] Furthermore, the temperature of the water cooling medium during the water cooling process is 15-30℃.

[0026] Compared with the prior art, this application has at least the following beneficial effects:

[0027] Based on further analysis and research of existing technical problems, this application uses an alternating magnetic field to make the distribution of precipitated phases in the finished alloy more uniform, effectively avoiding grain boundary embrittlement and inhibiting grain growth. It also induces strain-induced twinning, further optimizing the alloy's strength and plasticity. At the same time, through magnetic field-assisted multi-stage heat treatment, it promotes the strain-induced phase transformation from FCC to HCP, ultimately forming a finished alloy containing a two-phase structure of FCC and HCP, improving the alloy's work hardening ability and enhancing its plasticity. Attached Figure Description

[0028] Figure 1 This is a flowchart illustrating a method for synergistically improving the strength and plasticity of multi-component alloy laser additive manufacturing, provided as an embodiment of this application. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments.

[0030] like Figure 1 As shown, this application provides a method for synergistically improving the strength and plasticity of multi-component alloy laser additive manufacturing, which includes the following steps:

[0031] S1: The main alloy powder is prepared by various components, and then Si and Ti are made into intermediate alloy ingots in proportion. After crushing, they are mixed with the main metal. This ensures the uniform distribution of the refractory element Ti and avoids the risk of compositional fluctuation caused by directly adding pure metal. The components include Fe, Co and Ni elements. Fe serves as the matrix and constitutes the basic framework of the alloy. Co is used to increase the stacking fault energy, promote the formation of twins, and help improve the plastic deformation capacity of the material. Ni can stabilize the FCC phase and ensure that the alloy has good crystal structure stability. Si is used to improve the fluidity of the melt and reduce the generation of cracks during solidification. Ti is used to induce coherent L12-Ni3Ti nanoprecipitates to replace the traditional high-cost Al / Cr elements. Impurities are strictly controlled to avoid the formation of brittle phases.

[0032] The composition of Fe is 28-32% by mass, Co is 28-32% by mass, Ni is 36-40% by mass, Si is 0.08-0.2% by mass, and Ti is 0.04-0.1% by mass.

[0033] S1 specifically includes the following steps:

[0034] S1.1: Clean each component sequentially with acetone using ultrasonic cleaning for 15-20 minutes, rinse with deionized water, dehydrate with anhydrous ethanol, and then place in a vacuum drying oven to remove residual solvent. The temperature of the vacuum drying oven is 85-95℃, and the drying time is 2.5-3 hours.

[0035] S1.2: Using a planetary high-energy ball mill with zirconia ceramic balls as the grinding media, ball milling is performed for 4.5-5 hours under anhydrous ethanol protection, followed by sieving to obtain the main alloy powder with a particle size of 15–45 μm. Anhydrous ethanol helps prevent cold welding and excessive oxidation. The planetary high-energy ball mill speed is 300-350 rpm, and the ball-to-powder ratio is 10:1.

[0036] S1.3: Si and Ti powders with a mass ratio of 1:0.5 are unidirectionally pressurized to 300MPa in a steel mold and held for 5-10 minutes to form a cylindrical blank with dimensions of 30mm×10mm.

[0037] S1.4: Place the cylindrical blank in a vacuum sintering machine at a temperature of 800-850℃ (heating rate 5℃ / min) and hold for 1-1.2h to remove adsorbed gases; then raise the temperature to 1250-1300℃ (heating rate 10℃ / min) and hold for 2-2.2h to promote solid-phase reaction to synthesize a single titanium silicide phase. Cool to room temperature with the furnace to avoid thermal stress cracking.

[0038] S1.5: The cooled Si and Ti powders are initially crushed to <5mm particles using a jaw crusher, and then wet-milled (ethanol medium) using a planetary mill to obtain intermediate alloy powder with a particle size of <1mm.

[0039] S1.6: Add the main alloy powder to the ball mill, then add the intermediate alloy powder, and add 0.5% stearic acid. Dry ball mill for 1.2-1.5 hours at a speed of 200-250 rpm to break up agglomerates and improve interfacial wettability. Stearic acid is used to prevent electrostatic adsorption of the powder.

[0040] S2: During the laser selective melting and forming process, an ultra-high scanning speed of 25-30 m / s is used in conjunction with an ultra-thin layer thickness of 0.02 mm for layer-by-layer deposition. A 67° interlayer rotation strategy is employed to eliminate anisotropy, ultimately forming an alloy component with a honeycomb dislocation cell structure. The laser generator output power is 850–950 W, which effectively suppresses the evaporation loss of volatile elements (such as Ti) and maintains the stability of the alloy composition. Furthermore, the dense microstructure with uniform solid solution of Ti ensures a synergistic effect of strength and toughness in the material. Details are as follows:

[0041] Before initiating laser selective melting and forming, a worktable carrying pre-alloyed powder is first fed into the forming chamber, and a powder layer with a thickness of 0.02-0.04 mm is evenly spread using a scraper system. A high-purity argon gas protective environment (oxygen content <10 ppm) is then activated to prevent external air infiltration and ensure that the metal powder is not oxidized.

[0042] A point-by-point scanning mode combined with an ultra-high scanning speed of 25–30 m / s is employed to dynamically suppress the segregation behavior of trace elements such as Mn / Cr through rapid melting and solidification, promoting full diffusion and mixing of each element within the molten pool. After each layer is processed, the worktable descends by one layer thickness, repeating the powder-laying-scanning cycle until the component is formed. Throughout the process, a 67° interlayer rotation scanning strategy is strictly implemented. By alternating the energy input direction between adjacent layers, the crystallographic preferred orientation caused by unidirectional stacking is effectively eliminated, fundamentally improving the anisotropy problem of the material.

[0043] Simultaneously, during the molding process, a high-speed camera is used to capture the integrity of the melting trajectory, ensuring the controllable formation of the honeycomb-like dislocation cell structure. This unique microstructure originates from the combined effect of ultra-thin layer thickness and rapid solidification rate. When the laser sweeps across the powder bed at microsecond timescales, the intense temperature gradient induces a non-equilibrium solid-state transformation in local areas, ultimately forming substructural units with precisely controlled dimensions of 0.8–1.2 μm. Periodic shutdowns are used to sample and perform energy dispersive spectroscopy (EDS) analysis, focusing on detecting the solid solution state of Ti and the presence of unmelted particles.

[0044] S3: The alloy component is placed in a gradient temperature-controlled furnace and heated to 500-530℃, and held for 1.5-2 hours. Simultaneously, a 0.8T, 20Hz alternating magnetic field is applied to directionally drive the diffusion of Ti atoms, forming a uniformly distributed coherent L12-Ni3Ti nanoprecipitate phase, thus achieving precipitation strengthening. The alternating magnetic field inhibits grain boundary migration and avoids coarsening of the precipitate phase; the Si element reduces the surface tension of the melt, thereby increasing the solubility of Ti in the presence of Si.

[0045] When the alloy component is heated to 500-530℃ in a gradient temperature-controlled furnace, the oscillating electromagnetic field generated by the alternating magnetic field induces eddy current effects inside the metal. This continuously perturbs the lattice atomic arrangement through the Lorentz force, significantly reducing the diffusion activation barrier of Ti atoms and enabling Ti atoms to achieve exceptionally high mobility. Under this non-equilibrium state, Ti elements in the supersaturated solid solution rapidly accumulate in the defect-dense region, forming a uniformly distributed nanoscale Ni3Ti precipitate precursor.

[0046] The coherent L12-type Ni3Ti precipitates maintain a completely coherent relationship with the matrix (lattice mismatch <0.5%), and their (111) close-packed planes perfectly match the {111} planes of the FCC matrix. This atomically flat heterogeneous interface produces a dual strengthening effect: on the one hand, the shear modulus of the precipitates is 40% higher than that of the matrix, generating a stress field shielding effect under stress; on the other hand, the elastic strain field formed at the interface causes the surrounding dislocations to bend and multiply, achieving strengthening according to the Orowan mechanism. Transmission electron microscopy observations show that the spacing between the precipitates, with a size distribution of 15–25 nm, is precisely controlled within the range of 50–80 nm, which is exactly the optimal effective distance between the dislocation source and the barrier.

[0047] S4: Transfer the alloy sample that has undergone low-temperature aging treatment to the medium-temperature treatment zone of the gradient temperature-controlled furnace, raise the temperature to 780-800℃, and hold for 1.2-1.5 hours. Turn on the alternating magnetic field generator and apply a strong magnetic field of 1.2T and 10Hz, with the direction of the strong magnetic field along the key stress direction of the alloy component. This causes the strong magnetic field to interact with the atoms and electrons in the alloy, changing their bonding forces and motion states, effectively lowering the energy barrier of the strain-induced martensitic phase transformation from FCC to HCP, promoting the smooth initiation and acceleration of the phase transformation process, and laying the foundation for the formation of a specific microstructure.

[0048] By modulating phase transformation kinetics with an alternating magnetic field, the synergistic effect of nanoprecipitations and strain-induced twinning is achieved. The alternating magnetic field can accelerate element diffusion, promote the uniform distribution of nanoprecipitates, inhibit grain growth, and induce the formation of strain-induced twins, thereby further enhancing the strength and plasticity of the alloy.

[0049] S5: After the heat preservation is completed, the high-pressure nitrogen jet cooling device is quickly activated to perform water cooling treatment on the alloy components at a high-speed cooling rate of >150℃ / s, controlling the water cooling medium temperature to 15-30℃. Rapid cooling can suppress the excessive growth and coarsening of the martensitic phase, while ensuring that more than 60% of the FCC phase is retained in the alloy, promoting the strain-induced phase transformation of FCC→HCP, improving the work hardening ability of the alloy, enhancing the plasticity of the alloy, and finally forming a finished alloy product with a dual-phase structure containing FCC and HCP.

[0050] In subsequent deformation processes, the dual-phase structure can fully leverage the advantages of both phases, effectively enhancing the plasticity of the alloy through twin-coordinated dislocation movement, achieving a synergistic improvement in strength and plasticity, and giving the alloy superior comprehensive mechanical properties.

[0051] In the aforementioned method for synergistically enhancing the strength and plasticity of multi-component alloy laser additive manufacturing, an alternating magnetic field is used to make the distribution of precipitated phases in the finished alloy more uniform, effectively avoiding grain boundary embrittlement and inhibiting grain growth. This induces strain-induced twinning, further optimizing the strength and plasticity of the alloy. Simultaneously, through magnetic field-assisted multi-stage heat treatment, the strain-induced phase transformation from FCC to HCP is promoted, ultimately forming a two-phase alloy containing FCC and HCP, improving the work hardening ability and enhancing the plasticity of the alloy.

[0052] Here is a specific application example:

[0053] S1: Material preparation: Weigh 30% Fe, 32% Co, and 37.7% Ni as the base raw materials, and pre-alloy powder with 0.2% Si and 0.1% Ti.

[0054] S2: Selective Laser Melting: The prepared powder is loaded into the feeding system of the selective laser melting equipment. The laser power is set to 900W, the scanning speed to 28m / s, and the layer thickness to 0.02mm. A 67° interlayer rotation scanning strategy is used for layer-by-layer deposition. The stability of various parameters is closely monitored during the forming process to ensure the forming quality.

[0055] S3: Magnetic field-assisted preliminary heat treatment: The formed alloy component is placed in a device equipped with an alternating magnetic field generator and a gradient temperature-controlled furnace. First, a low-temperature aging treatment is performed, with the temperature set at 500℃, the time at 1.5h, and the magnetic field parameters at 0.8T and 20Hz.

[0056] S4: Medium-temperature phase transformation treatment: Heat to 750℃, hold for 1 hour and then quickly water cool. The magnetic field parameters are 1.2T and 10Hz to obtain the alloy product.

[0057] Comprehensive performance tests, including tensile and impact tests, were conducted on the samples after the above treatment. The test results showed that the sample achieved a yield strength of 980 MPa, an elongation of 32%, and an impact energy of 48 J, with all performance indicators meeting the expected targets. Microstructural analysis revealed the formation of a honeycomb-like dislocation cell structure, uniformly distributed coherent L12-Ni3Ti precipitates, and the occurrence of an FCC→HCP strain-induced phase transition within the sample.

[0058] Test Experiment Results Table

[0059]

[0060] The table above shows that the yield strength, elongation, and impact energy all meet or exceed the expected targets, indicating that the FeCoNi multi-component alloy product obtained by magnetic field-assisted multi-stage heat treatment achieves a synergistic improvement in strength and plasticity.

[0061] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

Claims

1. A method for synergistically improving the strength and plasticity of multi-component alloy laser additive manufacturing, characterized in that, The method includes the following steps: S1: The main alloy powder is prepared by various components, and then Si and Ti are made into intermediate alloy ingots in a certain proportion, which are crushed and mixed with the main metal. The components include Fe, Co and Ni elements, with Fe at a mass of 28-32%, Co at a mass of 28-32%, Ni at a mass of 36-40%, Si at a mass of 0.08-0.2%, and Ti at a mass of 0.04-0.1%. S2: During the laser selective melting and forming process, an ultra-high scanning speed of 25-30 m / s is combined with an ultra-thin layer thickness of 0.02 mm for layer-by-layer deposition, and an anisotropy is eliminated by a 67° interlayer rotation strategy; finally, an alloy component with a honeycomb dislocation cell structure is formed. S3: Place the alloy component in a gradient temperature-controlled furnace and heat it to 500-530℃, holding it at that temperature for 1.5-2 hours. Simultaneously, start an alternating magnetic field to directionally drive the diffusion of Ti atoms, forming a uniformly distributed coherent L12- Ti nano-precipitates; The alternating magnetic field has parameters of 0.8T and 20Hz, which is used to suppress grain boundary migration and prevent coarsening of precipitates. S4: Transfer the alloy sample that has undergone low-temperature aging treatment to the medium-temperature treatment area of ​​the gradient temperature control furnace, heat it to 780-800℃, and hold it for 1.2-1.5h. Turn on the alternating magnetic field generator and apply a strong magnetic field. The strong magnetic field parameters are 1.2T and 10Hz, and the direction of the strong magnetic field is arranged along the key stress direction of the alloy component. It is used to make the strong magnetic field interact with the atoms and electrons in the alloy, thereby changing the binding force and motion state of the atoms and electrons. S5: After the heat preservation is completed, the high-pressure nitrogen jet cooling device is quickly started to water-cool the alloy components at a high-speed cooling rate of >150℃ / s, and finally a duplex alloy product containing FCC and HCP is formed.

2. The method for synergistic improvement of strength and plasticity in multi-component alloy laser additive manufacturing according to claim 1, characterized in that, S1 specifically includes the following steps: S1.1: Clean each component sequentially with acetone using ultrasonic cleaning for 15-20 minutes, rinse with deionized water, dehydrate with anhydrous ethanol, and then place in a vacuum drying oven to remove residual solvent. The temperature of the vacuum drying oven is 85-95℃, and the drying time is 2.5-3 hours. S1.2: Using a planetary high-energy ball mill with zirconia ceramic balls as the grinding medium, the ball mill is carried out for 4.5-5 hours under the protection of anhydrous ethanol, and then sieved to obtain the main alloy powder with a particle size of 15-45μm. S1.3: Si and Ti powders with a mass ratio of 1:0.5 are unidirectionally pressurized to 300MPa in a steel mold and held for 5-10 minutes to form a cylindrical blank with dimensions of 30mm×10mm; S1.4: Place the cylindrical blank in a vacuum sintering machine at a temperature of 800-850℃ and hold for 1-1.2 hours to remove the adsorbed gas. Then raise the temperature to 1250-1300℃ and hold for 2-2.2 hours. S1.5: The cooled Si and Ti powders are initially crushed to <5mm particles using a jaw crusher, and then wet-ground to <1mm particle size using a planetary mill to obtain intermediate alloy powder. S1.6: Add the main alloy powder to the ball mill, then add the intermediate alloy powder, and add 0.5% stearic acid. Dry ball mill for 1.2-1.5 hours at a speed of 200-250 rpm.

3. The method for synergistic improvement of strength and plasticity in multi-component alloy laser additive manufacturing according to claim 2, characterized in that, The stearic acid is used to prevent electrostatic adsorption of the powder.

4. The method for synergistic improvement of strength and plasticity in multi-component alloy laser additive manufacturing according to claim 1, characterized in that, The laser generator has an output power of 850-950 W. Before starting the laser selective melting and forming, the worktable carrying the pre-alloy powder is first sent into the forming chamber, and a powder layer with a thickness of 0.02-0.04 mm is evenly spread by the scraper system.

5. The method for synergistic improvement of strength and plasticity in multi-component alloy laser additive manufacturing according to claim 1, characterized in that, When the alloy component is heated to 500-530°C in a gradient temperature-controlled furnace, the oscillating electromagnetic field generated by the alternating magnetic field will induce eddy current effects inside the metal, continuously disturbing the arrangement of lattice atoms through the Lorentz force, and reducing the diffusion activation barrier of Ti atoms.

6. The method for synergistic improvement of strength and plasticity in multi-component alloy laser additive manufacturing according to claim 1, characterized in that, The temperature of the water cooling medium during the water cooling process is 15-30℃.

Citation Information

Patent Citations

  • A high thermal conductivity and high strength Co-Fe-Ni alloy for molds and its additive manufacturing method.

    CN112301255B

  • Thermo-magnetic coupling field cooperated selective laser-melting device and heating method thereof

    CN108421976A

  • Laser material addition manufacturing method and device of congruent axialite metal component

    CN108620584A